Changes in fungal community during different phases in conventional and bioreactor composting systems according to metatranscriptomics analysis. (14th December 2022) - Ding, Jianli; Wei, Dan; An, Zhizhuang; Jin, Liang; Wu, Fengxi; Suo, Linna; Wang, Lei; Li, Yan; Cai, Shanshan
Abstract: We determined the changes that occurred in fungal community structures and their functions in conventional and bioreactor composting systems. The Illumina MiSeq platform was employed to sequence cDNA by reverse transcription to conduct metatranscriptomics analysis of RNA, and the FUNGuild tool was applied. The α-diversity of fungi in the bioreactor composter increased throughout composting, especially in the initial three phases, but decreased in the conventional composting system. The three dominant phyla in the bioreactor system were Ascomycota (30.27%–68.50%), Mortierellomycota (3.81%–39.51%), and Basidiomycota (9.17%–30.86%). Ascomycota (76.96%–97.18%) was the main phylum in the conventional composting system. Mortierella, Guehomyces, Plectosphaerella, Chaetomium, Millerozyma, and Coprinopsis were the main genera in the bioreactor composter. In the same phase, significant differences in the fungal functions were found between the two composting methods. Available phosphorus was the main factor that affected the community structures and functions of fungi in the bioreactor composter.